NATURAL GAS AS AN ALTERNATIVE FUEL OF DIESEL FOR GENERATION POWER PLANTS - Ibrahim M. Abou El Leil; Seham N. Tawfic; Somaya A. Altayeb (Surman Journal of Science and Technology, 2024)
This study aims to explore the possibility of using flared natural gas as a cheaper and more eco-friendly alternative to diesel fuel at the Tobruk gas power station, since it is readily available from oil and gas fields in Libya. The utilization of gas flare of two gas fields namely Faregh and El Ragouba gas fields have been highlighted. The physical and chemical properties of natural gas and diesel from Faregh and El Ragouba gas fields will be evaluated to assess their suitability for power generation. Data on daily gas flaring volumes is analyzed to evaluate the potential for energy recovery, while the economic feasibility of using flared natural gas as an alternative to diesel is assessed and Faregh and El Ragouba gas fielded. The total gas being flared in the two fields are approximately 6.350 and 0.18 MMSCF/D respectively. The daily output from flare natural gas of Faregh and El Ragouba gas fields gives a significant values of power generation comparing with diesel fuel. Also, the total energy from flare natural gas per day for both gas fields regarded as reliable values as alternative fuel. The calculating heating values of flare natural gas for Faregh and El Ragouba gas fields are 7329.15 Btu/scf and 1248.94 Btu/scf respectively. These values indicate that they fall within the required specifications for the heating value of natural gas fuel used in power plant turbines. Additionally, the Wobbe Index values are consistent with the typical range specified in the literature on natural gas turbine specifications.